2019
DOI: 10.1136/bmjopen-2019-030175
|View full text |Cite
|
Sign up to set email alerts
|

Cluster randomised controlled trial to investigate the effectiveness and cost-effectiveness of a Structured Health Intervention For Truckers (the SHIFT study): a study protocol

Abstract: IntroductionHeavy goods vehicle (HGV) drivers exhibit higher than nationally representative rates of obesity, and obesity-related comorbidities, in comparison to other occupational groups. Their working environments are not conducive to a healthy lifestyle, yet there has been limited attention to health promotion efforts. We have developed a Structured Health Intervention For Truckers (the SHIFT programme), a multicomponent, theory-driven, health-behaviour intervention targeting physical activity, diet and sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 64 publications
0
12
0
Order By: Relevance
“…This article utilizes data collected from the SHIFT trial, which adopted a cluster RCT design and involved truck drivers from 25 transport sites located throughout the Midlands region of the United Kingdom. Comprehensive details of the full trial protocol and measurements have been reported elsewhere 10,19 . After providing informed consent, participants completed a 2-hour health assessment (0 months; detailed below) and were then randomized at the cluster level into the control or intervention arm.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…This article utilizes data collected from the SHIFT trial, which adopted a cluster RCT design and involved truck drivers from 25 transport sites located throughout the Midlands region of the United Kingdom. Comprehensive details of the full trial protocol and measurements have been reported elsewhere 10,19 . After providing informed consent, participants completed a 2-hour health assessment (0 months; detailed below) and were then randomized at the cluster level into the control or intervention arm.…”
Section: Methodsmentioning
confidence: 99%
“…Full details of all measurements are reported elsewhere 10,19 . Briefly, participants were asked to fast from all food and drink (except water) for at least 4 hours before the health assessment.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, long-haul truckers operate tractor-trailers and are sedentary for extended periods of time, and combating obesity and chronic health issues have been a focus for these workers. [23][24][25][26] Chronic diseases, especially heart disease, contribute to the largest healthcare expenditures in the United States and these are major issues for employers, as well. [27][28][29] Research has shown that improving modifiable cardiovascular risk factors greatly reduces the risk of coronary heart disease.…”
Section: Introductionmentioning
confidence: 99%